Human Endogenous Retroviruses as Pathogenic Factors in the Development of Schizophrenia - Slokar, Gorjan; Hasler, Gregor (Frontiers in Psychiatry, 2016)
Schizophrenia is a complex disorder, characterized by the interplay between genetic and environmental factors. Human endogenous retroviruses (HERVs), genetic elements that originated from infections by exogenous retroviruses millions of years ago, comprise ~8% of the human genome. Here, we provide a comprehensive review of accumulating evidence, detailing HERV aberrancies associated with schizophrenia. Studies examining the genome, transcriptome, and proteome of individuals with schizophrenia provide data that support the association of these viral elements with the disorder. Molecular differences can be found within the central nervous system (CNS) and peripheral tissues. However, additional studies are needed to substantiate the reported link and to address several discrepancies among previous investigations. We further discuss potentially relevant pathogenic mechanisms to the development of schizophrenia.